Acute Effects and the Dreamy State Evoked by Deep Brain Electrical Stimulation of the Amygdala: Associations of the Amygdala in Human Dreaming, Consciousness, Emotions, and Creativity - Lai, George; Langevin, Jean-Philippe; Koek, Ralph J.; Krahl, Scott E.; Bari, Ausaf A.; Chen, James W. Y. (Frontiers in Human Neuroscience, 2020)
Accurate localization of complex human experiences such as emotions, dreaming, creativity, and consciousness to specific cerebral structures or neural networks has remained elusive despite technological advances. We report the use of acute deep brain stimulation to evoke behavioral and emotional effects by applying electrical stimulation at various voltage strengths to the basolateral and central subnuclei of the amygdala in addition to the head of hippocampus for 2 subjects with medically refractory post-traumatic stress disorder. Our results suggest that the amygdala could be a node in a neural network responsible for the generation of complex vivid mental imagery and integrated sensory experiences similar to John Hughlings Jackson’s “dreamy state” and “double consciousness,” which have been classically associated with temporal lobe epilepsy during uncinate seizures. That we were able to elicit similar vivid, dynamic, complex, bizarre, and original mental imagery with electrical stimulation in non-epileptic subjects suggests that Jackson’s seizure related “dreamy state” and “double consciousness” may arise from heightened innate brain mechanisms with the amygdala acting as a node in the neural network responsible for physiologic dreaming and creative functions. Furthermore, our subjects experienced different emotions with different stimulation strengths at various electrode contacts. Our results suggest that higher voltage stimulation of the amygdala and hippocampus at 4-5V leads to predominantly negative responses and 2-4V stimulation showed inversely coupled positive and negative responses of the amygdala in either hemisphere which may imply hemispheric dominance of emotional valences without relation to handedness. Due to the unique and complex responses dependent on location and strength of stimulation, we advise that all patients receiving deep brain stimulation of the amygdala undergo acute stimulation mapping in a monitored setting before selecting therapeutic parameters for chronic stimulation.